2023
DOI: 10.1002/dro2.77
|View full text |Cite
|
Sign up to set email alerts
|

Hydrovoltaic energy from water droplets: Device configurations, mechanisms, and applications

Luxian Li,
Xiang Wang,
Wei Deng
et al.

Abstract: Water, the source of life, contains immense energy and manifests in diverse forms. Hydrovoltaic technology enables the direct interaction between water and materials to generate electricity, a vital necessity for industry modernization. Due to the ubiquitous presence and easy availability of falling water, hydrovoltaic energy derived from water droplets has attracted considerable attention and shown great potential in raindrop energy harvesting. In this review, a comprehensive summary of the latest advancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…We recently discovered the pivotal role of capillary front, by broadening which we obtained a ~5 V output of a single unit, much higher than previously reported results, and achieved integrated kilovolt level output in a water-film operation mode [24]. Water droplet and waving induced electricity was firstly found on monolayer graphene [25][26][27], termed as drawing potential and waving potential, and then revives in fluoropolymers (e.g., PTFE and FEP) based systems for rain droplets and water flowing in tubes involving bulk effect [28][29][30][31][32][33][34][35][36]. Moisture-based electricity generation converts chemical potential energy derived from moisture diffusion when water molecules contact with hydroscopic materials [37].…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…We recently discovered the pivotal role of capillary front, by broadening which we obtained a ~5 V output of a single unit, much higher than previously reported results, and achieved integrated kilovolt level output in a water-film operation mode [24]. Water droplet and waving induced electricity was firstly found on monolayer graphene [25][26][27], termed as drawing potential and waving potential, and then revives in fluoropolymers (e.g., PTFE and FEP) based systems for rain droplets and water flowing in tubes involving bulk effect [28][29][30][31][32][33][34][35][36]. Moisture-based electricity generation converts chemical potential energy derived from moisture diffusion when water molecules contact with hydroscopic materials [37].…”
Section: Introductionmentioning
confidence: 72%
“…Water droplet spreading or sliding on dielectric layers, together with well-configured electrodes, can output electricity through electrostatic induction, thus converting mechanical energy into electricity [28][29][30][31][32][33]. In this work, to exploit the rotary motion of the "evaporation motor", we designed a water-droplet based generator, where a water column was encapsuled in a concentric annular FEP tube (Fig.…”
Section: Rotational Motion Driven Water Droplet-based Electricity Gen...mentioning
confidence: 99%
See 1 more Smart Citation
“…198 This electricity generation, driven by electrokinetic effects, can harness energy wherever a water flow comes into contact with a charged solid, owing to the pressuredriven transport of counterions in the electrical double layer 199 and has been used for the development of different devices that harvest energy from water in the form of raindrops. [200][201][202][203] Electrified liquid water-solid interfaces [204][205][206] including biosurfaces 207 deliver electric current, in many ways. 208,209 Moving a 0.6 mL aqueous (NaCl 0.6 M) single droplet on a graphene/polytetrafluorethylene surface produces an output power of 1.9 mW 210 while raindrops 211 on fluorinated superhydrophobic greenhouse-modified films give a maximum output power density of 38 mW m À2 through a 16 MO load resistance.…”
Section: Mechanochemical Reactions and Catalysis: The Interplay Betwe...mentioning
confidence: 99%
“…1,2 Recently, hydrovoltaic power generators (HPGs) have been developed based on the interactions between functional materials and water molecules through capillary infiltration, evaporation, or moisture. 3–6 Similar to biological systems, the energy coupling and signal transmission mechanisms in HPGs are intricately linked to selective ion/molecule transport. 7–10 In 2017, Guo et al reported the inaugural work using the interactions between water molecules and a porous carbon-black film for HPGs, achieving a sustained open-circuit voltage ( V oc ) of 1 V and a short-circuit current density ( I sc ) of 60 nA cm −2 .…”
Section: Introductionmentioning
confidence: 99%